The Links between traditional Valachian vocal music from the Carpathians and the Balkans in the context of historical Valachian migrations. - Cząstka-Kłapyta, Justyna Małgorzata (Balcanica Posnaniensia. Acta et studia, 2021)
The musical culture of the Aromanians, and other Valachian-origin groups, was constantly subjected to acculturation and dynamic adaptation. These groups have preserved certain timeless, circulating musical constructs most likely influencing the architecture of the song melody, performance style and music-making patterns, which can be considered as a common idiom of the Walachian vocal tradition. The common features of the Balkan (Aromanian) and Carpathian (Valachian) vocal heritage are: natural harmonic hearing expressed in the tendency to sing without instrumental accompaniment, or with its participation in a heterophonic form. Polyphonic singing forms are characterized by a vocal hierarchy combined with a sensitivity to the acoustics of sound, which manifests itself in specific performance manners (slow pace, performance freedom, long breathing phrases, glissanding, etc.). The Valachian idiom of inter-voice chords is defined by the intervals of fourths, fifths, octaves and dissonances - especially seconds. The greatest similarities are especially visible between the vocal repertoire of Carpathian Ruthenians and Aromanians, also in relation to the scale, the morphology of the song melody (e.g. tetrachordal and pentachordal structure of phrases, the primary meaning of the fourth, the tendency to descendental phrases) and to descendental rhythmic punctuated and inversely scored. The common Valachian musical heritage also includes musical instruments such as: fujara, duda / gajda, trembita, dwojnica, which music scale and melody contributed to the unification of diverse and geographically distant vocal dialects along with their ritual-magic background related with pastoral lifestyle. Singing for voices is considered as a basic feature of ethnic identity, and as a tool of communication and social integration within the present-day Valachian ethnoses. The survival of the unique polyphonic singing practice may be related to migratory nature of Valachian lifestyle as well as relative cultural and geographical isolationism of mountain areas together with the scattered nature of the Valachian settlement. Differences between the Carpathian and Balkan polyphony may have been related to the crushing of archaic polyphonic forms (drones), which in Carpathians have survived mainly on the instrumental grounds. The performance manners and the archaic repertoire associated with drones were influenced by East Slavic variation heterophony, and then medieval polyphonic technique (discantus) disseminated in Catholic and Orthodox churches during the Valachian migration period. Finally, the major-minor harmonics, contributed to the disappearance of polyphonic structures and the flattening of Valachian vocal idioms.